Association of Arthritis Onset with Influenza: Analysis of the Canadian Early Inflammatory Arthritis Cohort. Issue 1 (15th March 2019) - Kudaeva, Fatima; Speechley, Mark; Klar, Neil; Schieir, Orit; Bartlett, Susan J.; Bessette, Louis; Boire, Gilles; Hazlewood, Glen; Hitchon, Carol A.; Keystone, Edward; Tin, Diane; Thorne, Carter; et al.
Abstract : Objective: To evaluate seasonal patterns of early inflammatory arthritis (IA) onset and potential associations with IA symptom onset. Methods: The Canadian Early Arthritis Cohort (CATCH) is an inception cohort study of adults with early (12 months or less) IA. We used patient reports of symptom onset as a proxy of IA onset and examined the seasonal distribution of IA onset over 10 years. Influenza time series was based on laboratory‐confirmed influenza A and B from the Canadian FluWatch surveillance from 2010‐2016. Bivariate analysis of influenza and IA was performed using cross‐correlations with different time lags and Poisson regression. IA and influenza were recorded as monthly total frequencies. Results: Of 2519 IA patients, 88% had confirmed rheumatoid arthritis (RA). Significantly, more IA onsets occurred in winter compared with other seasons (P = 0.03); although IA onset was more frequent in January, the difference between months was not statistically significant. Compared to months with the lowest influenza rates, months with the highest influenza rates had a statistically significant, but trivial, increase of 0.003% in the incidence of IA (incidence rate ratio (95% confidence interval): 1.00003 (1.00005; 1.000053), P = 0.02). Conclusion: Although IA symptom onset occurs more frequently in winter, we found that flu outbreaks were not associated with a meaningful increase in IA symptom onset in a large, well‐characterized cohort of Canadian adults over 6 years.